Exploring teaching staff's narratives about the use of Solution Circles to support pupils with Social Emotional and Mental Health (SEMH) needs - Kemp, Katie (2020)
Background: Solution Circles (SCs) are a collaborative group consultation approach based on the principles of inclusion (Forest & Pearpoint, 1996). One of the most prominent issues regarding inclusion in education is how we support children who have Social, Emotional and Mental Health (SEMH) needs (British Psychological Society [BPS], 2002). Young people with SEMH needs report teachers as their most common source of support (Meltzer, Gatward, Goodman, & Ford, 2000). Research has found addressing SEMH needs can be emotionally and physically exhausting for teachers (Cole, 2010), and is a primary factor in teacher burnout (Bauer et al., 2006). However, the opportunity for teachers to reflect through narrative peer support groups and group consultations has been recognised as a key source of support when working with pupils with SEMH needs (Rae, Cowell & Field, 2017; Davison & Duffy, 2017). There is limited empirical evidence concerning group consultation approaches (Bennet & Monsen, 2011) and currently, only two published studies on SCs (Grahamslaw & Henson, 2015).